The Movers of Islamization: Studies on the Islamization of the Coastal and Interior of the Archipelago in the XIII - XIX centuries - Ramadhan, syahril; Budianto, Aan (Universitas Islam Negeri Raden Intan Lampung, 2022)
Islamization is an important part of the long history of the land under the wind of the archipelago. This incident has become a turning point for various social changes in the archipelago. Lombard called this the emergence of a new society, while Ricklefs called it the emergence of the modern age. This article will explain about the drivers of Islamization who have had a major influence on the growth of a new, modern society from the 13th to 19th centuries. This study focuses on discussing the drivers of Islamization both on the coast and in the interior, along with the characteristics of the movements and the roles they were given. The data used are in the form of books as well as those published from various sources which the author then arranges chronologically in the form of historical stories (historiography). The results of this study are that Islamization is carried out through two main drivers who have roles in their respective places, namely in the coast and inland.